Log in to add a comment

## Answers

**Solutions**

Let's solve for a.

a/ax−1+b/bx−1=a+b

**Step 1: Flip the equation.**

a+b=2x−2

**Step 2: Add -b to both sides.**

a+b+−b=2x−2+−b

a=−b+2x−2

**Answer:**

a=−b+2x−2

≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡

**Let's solve for b.**

a/ax−1+b/bx−1=a+b

**Step 1: Flip the equation.**

a+b=2x−2

**Step 2: Add -a to both sides.**

a+b+−a=2x−2+−a

b=−a+2x−2

**Answer:**

b=−a+2x−2

≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡≡

**Let's solve for x.**

a/ax−1+b/bx−1=a+b

**Step 1: Add 2 to both sides.**

2x−2+2=a+b+2

2x=a+b+2

**Step 2: Divide both sides by 2.**

x=1/2a+1/2b+1

**Answer:**

x=1/2a+1/2b+1